The satisfaction of students towards facilities provided by UiTM Perak / Nur Farahana Ismail and Haryati Mohd Isa - Ismail, Nur Farahana; Mohd Isa, Haryati (2021)
There are many types of amenities that we inevitable to use in our daily life. As well as in university life. But, it doesn't mean that all the facilities can fulfill all students' needs in their daily life. Even though some might say that the satisfaction is just a brief feeling that have in everyone's self, it is important to be contented to achieve its anticipations (I.M. Salinda Weerasinghe et. al, 2017). The endowment of good facilities and accommodations to universities and any other level of educations should be taken care efficiently by the Ministry of Education (Kementerian Pendidikan). Satisfaction of students is one of the critical issues that arise and need to be considered to make sure that students are comfortable being around the campus. In this paper there are two (2) research objectives which are 1) to identify the types of students facilities provided in UiTM Perak, and 2) to investigate the level of satisfaction among UiTM Perak students towards facilities provided in UiTM Perak. This paper will be focused on the students' satisfaction level towards the facilities provided in UiTM Perak, Seri Iskandar Campus. The data collection will be taken care by using the survey questionnaire that will be dispersed through Google Form only because of the limitation on the current pandemic that restricted us to move around and need to follow the Movement Control Order (MCO). The paper will be focusing only to the post graduate students due to the limitations of some facilities for their studies. This automatically can assure that UiTM Perak could extemporize their credibility in handling the issues concerning about the students' welfares.